The Impact of COVID‐19‐Related School Closures on Student Achievement—A Meta‐Analysis - König, Christoph; Frey, Andreas (Educational measurement, issues and practice, 2022)
COVID‐19 led to school closures and the necessity to use remote learning in 2020 and 2021 around the globe. This article provides results for a three‐level random‐effects meta‐analysis examining the average effect of the COVID‐19‐related school closures with respect to several moderator variables. The results showed a robust average effect of d=−0.175(SE=0.063$d = - 0.175( SE = 0.063$, p=0.013,95%CI[−0.308,−0.041])$p = 0.013,95% {\rm{CI}}[ { - 0.308, - 0.041} ] )$. The moderator analysis was largely insignificant; however, the results tentatively point out that younger students in schools were more negatively affected compared to older students, and that the negative effect reduced with subsequent lockdowns in autumn and winter 2020/2021. The results are discussed with respect to potential explanations.